2000
DOI: 10.18785/goms.1801.01
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Monitoring of Submerged Aquatic Vegetation in Escambia-Pensacola Bay System, Florida

Abstract: Recently, the distribution and changes in submerged aquatic vegetation (SAY) in the Escambia-Pensacola Bay System in northestern Florida were monitored by two techniques. One technique used divers to measure changes in the deepwater margin of beds and provided horizontal growth measurements to the nearest centimeter, the other used a differential global positioning system (DGPS) on a small boat to map the perimeter of SAY beds in shallow water. Current distribution of SAY in Escambia Bay shows that most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…The area in upper Escambia Bay where bottom light levels are ≥20% is calculated as 3.8 km 2 , which is similar to the seagrass bed area estimate of 1.5 km 2 observed in 1992 (Lores et al, 2000;Lores and Sprecht, 2001). The area in upper Escambia Bay where bottom light levels are ≥20% is calculated as 3.8 km 2 , which is similar to the seagrass bed area estimate of 1.5 km 2 observed in 1992 (Lores et al, 2000;Lores and Sprecht, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…The area in upper Escambia Bay where bottom light levels are ≥20% is calculated as 3.8 km 2 , which is similar to the seagrass bed area estimate of 1.5 km 2 observed in 1992 (Lores et al, 2000;Lores and Sprecht, 2001). The area in upper Escambia Bay where bottom light levels are ≥20% is calculated as 3.8 km 2 , which is similar to the seagrass bed area estimate of 1.5 km 2 observed in 1992 (Lores et al, 2000;Lores and Sprecht, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…In a detailed study conducted in these areas (Heck et al 1996), seagrasses declined during 1993 -1995 in both areas due to a combination of propeller scarring, reduced water clarity, changes in salinity and burial due to hurricanes. Lores et al (2000) reported seagrass coverage was also decreasing in Big Lagoon during 1997 and 1998.…”
Section: Historical Perspectivementioning
confidence: 96%
“…The numerous seagrass investigations conducted in the PBS have been temporally and spatially inconsistent and research methodologies have varied. Seagrass mapping has been the focus of most studies, and only limited information is available describing physiological and morphological parameters of plant condition such as above-and belowground biomass, shoot density, blade height and epiphyte/ biomass ratio, which have been reported for grasses in Big Lagoon, Santa Rosa Sound and Escambia River delta region (Heck et al 1996, Lores et al 2000, FDEP 2001.…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Although SAV distributions in some regions of the Gulf have been reported (e.g., Iverson and Bittaker, 1986;Handley et al, 2007;Mills et al, 2008), to date (Appendix) there has been no comprehensive Gulf-wide survey of mesohaline (5-20 ppt) SAV distribution. Most SAV studies in the Gulf have focused on marine SAV (seagrasses and macroalgae) that occur in large beds in clear waters near beaches, barrier islands, and open bays (Continental Shelf Associates, Inc., and Martel Laboratories, Inc., 1985;Lores et al, 2000). These seagrass beds are the SAV habitat reported in estimates of the nation's natural resources (e.g., Duke and Kruczynski, 1992;Mattson, 1999).…”
Section: Introductionmentioning
confidence: 99%